(untitled) (African Journal of Biomedical Research, 2023)
The widespread resistance to current antimalarial agents adds to the great burden of malaria. This study evaluated the antimalarial activity of novel compounds against the Plasmodium falciparum NF54 chloroquine-sensitive strain individually and combined with quinine using the parasite lactate dehydrogenase (pLDH) assay. Furthermore, toxicity screening was carried out to evaluate the safety profile of the derivatives. All twenty-seven chloroquine acetamide hybrids possessed antimalarial activity (IC50 range: 1.29 – 53.98 µM), while proving to show no toxicity against host red blood cells. The derivatives showed a good safety profile with low toxicity to human embryonic kidney epithelial cells (% inhibition average: 1.93-53.85%) and minimal lethality to brine shrimp (0-4.7%). None of the compounds demonstrated inhibitory effects on the Anopheles arabiensis mosquito larvae. The two most active derivatives displayed favorable ionization properties and synergistic activity in combination with quinine. In morphological studies carried out over a period of 48 hours, the most active derivative showed similar schizonticidal activity as the standard quinine with a lag in progression from the trophozoite stage. The most active derivative CQPA-26 has good antimalarial activity and low toxicity worth being explored with further structural modifications which may increase antimalarial activity.